1994
DOI: 10.1128/jb.176.12.3820-3823.1994
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a yeast intron-containing tRNA in the archaeon Haloferax volcanii

Abstract: Expression of the yeast tRNAPro(UGG) gene in Haloferax volcanii resulted in the production of a single stable transcript that had not undergone intron processing or processing of 5' and 3' flanking sequences. Mutation of the exon-intron boundary region of this RNA to produce a precursor RNA with the preferred halobacterial consensus exon-intron boundary structure did not restore intron processing. Processing of 5' and 3' flanking sequences was restored when the acceptor stem U6-U67 pair was changed to A6-U67. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…We have previously shown that a 48-bp DNA fragment originating from the 5Ј region of the H. volcanii tRNA Lys gene is capable of directing efficient and precise transcription when introduced into these cells on plasmid pWL201 (39). Using the archaeal box A consensus (41,47,48,51) as a guide, combined with the observation that box A elements are generally located approximately 25 bp 5Ј of the transcription initiation site, we identified the sequence 5Ј-ATTTTACCCAC-3Ј as a potential box A element within the tRNA Lys DNA fragment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that a 48-bp DNA fragment originating from the 5Ј region of the H. volcanii tRNA Lys gene is capable of directing efficient and precise transcription when introduced into these cells on plasmid pWL201 (39). Using the archaeal box A consensus (41,47,48,51) as a guide, combined with the observation that box A elements are generally located approximately 25 bp 5Ј of the transcription initiation site, we identified the sequence 5Ј-ATTTTACCCAC-3Ј as a potential box A element within the tRNA Lys DNA fragment.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Transcription from this promoter begins within the expected box B element and results in the production of a single stable transcript that can be detected by Northern (RNA) analysis (37,39).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cct1 and cct2 5Ј flanking sequences were cloned into the plasmid pWL201 expression vector (39) as HindIII-XbaI fragments. In the case of cct1, whose 5Ј flanking region contained a HindIII endonuclease restriction site, the putative core promoter region was first cloned into the HindIII and XbaI sites of pWL201, and then the remaining upstream sequence was ligated into the expression construct as a HindIII-HindIII fragment.…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes remove the intron by making two independent endonucleolytic cleavages. It is generally accepted that the archaeal enzymes act without any reference to the mature domain but instead recognize specific structures that define the intron-exon boundaries (6)(7)(8). By contrast, the eukaryal enzyme normally acts in a mature-domain-dependent mode (3,4).…”
mentioning
confidence: 99%